Clustered allocation as a way of understanding historical controls: Components of variation and regulatory considerations. (July 2020) - Collignon, Olivier; Schritz, Anna; Senn, Stephen J; Spezia, Riccardo
There has been increasing interest in recent years in the possibility of increasing the efficiency of clinical trials by using historical controls. There has been a general recognition that in replacing concurrent by historical controls, the potential for bias is serious and requires some down-weighting to the apparent amount of historical information available. However, such approaches have generally assumed that what is required is some modification to the standard inferential model offered by the parallel group trial. In our opinion, the correct starting point that requires modification is a trial in which treatments are allocated to clusters. This immediately shows that the amount of information available is governed not just by the number of historical patients but also by the number of centres and of historical studies. Furthermore, once one accepts that external patients may be used as controls, this raises the issue as to which patients should be used. Thus, abandoning concurrent control has implications for many aspects of design and analysis of trials, including (a) identification, pre-specification and agreement on a suitable historical dataset; (b) an agreed, enforceable and checkable plan for recruiting the experimental arm; (c) a finalised analysis plan prior to beginning the trial and (d) use of a hierarchical model with sufficient complexity. We discuss these issues and suggest approaches to design and analysis making extensive reference to the partially randomised Therapeutic Arthritis Research and Gastrointestinal Event Trial study. We also compare some Bayesian and frequentist approaches and provide some important regulatory considerations. We conclude that effective use of historical data will require considerable circumspection and discipline.